EFEKTIVITAS METODE SHOT BLOCKER DAN HELFER SKIN TAP KOMBINASI ASI TERHADAP RESPON NYERI BAYI PADA IMUNISASI PENTAVALEN - Atikah, Atikah; Sumarni, Sri; Simbolon, Demsa (Poltekkes Kemenkes Bandung, 2025)
Immunization injections are often the main cause of pain in babies, which can cause anxiety and discomfort for both the baby and the family. Pain due to vaccination can affect the baby's heart rate, oxygen saturation, breathing, pain sensitivity, and neurological development. Therefore, efforts to reduce pain in infants have the potential to prevent fear of needles and increase satisfaction and trust in health services. Non-pharmacological methods, such as the use of Shot Blocker and Helfer Skin Tap combined with ASI, are methods that help reduce pain during immunization injections. The study aimed to test the effectiveness of the combination of Shot Blocker and Helfer Skin Tap methods combined with ASI in reducing the pain response in babies during Pentavalent immunization and analyzing the founding variables in influencing the baby's pain response. This study was a true experiment study with posttest-only control group design. The sampling technique was simple random sampling by using RAND in Microsoft Excel, so the sample size was 78 divided into 3 groups namely the Shot Blocker group with a combination of breast milk, the Helfer Skin Tap group with a combination of breast milk, and the breastfeeding group. The analysis test used Wilcoxon test and Ancova test. The result showed there was a significant difference in pain response between the intervention group and the control group with a p-value=0.000. The study concluded Shot Blocker method combined with ASI was more effective in reducing pain than the Helfer Skin Tap method combined with ASI, with p-value=0.001.